The discovery of the subgenus Contochorus van Achterberg, 1976 (Hymenoptera, Braconidae, Brachistinae, Blacini, Blacus) in China - Lu, Qian-Yu; Achterberg, Cornelis Van; Tang, Pu; Chen, Xue-Xin (Zootaxa, 2023)
The subgenus Contochorus van Achterberg, 1976 (Hymenoptera, Braconidae, Blacus) is newly recorded from China. Two new species are proposed, B. (C). capillosus sp. nov., B. (C). planus sp. nov., and two species are newly recorded in China, B. (C). mellitarsis van Achterberg, 1988 and B. (C). turbidus Papp, 1985. An updated key to the currently known species of the subgenus Contochorus in the world is provided.